Caracterização de dispositivos a base de Pani e Pedot: PSS impressos por impressora jato de tinta visando aplicações como sensores - Morais, Rogério Miranda [UNESP] (2015)
This work presents the production and characterization of humidity sensors and fully printed ammonia, using an inkjet printer commercial. Inks of PANIN and PEDOT:PSS were prepared and printed using an HP Deskjet D2460 printer. Films of the conducting polymer PEDOT:PSS was printed on paper and plastic substrates and their morphological and electrical properties were evaluated in function of the surface density of printed material and roughness of the substrate in order to obtain printed films with sufficient electrical current to operate as electrodes. Films of PANI, with different number of prints, were printed between the electrodes of PEDOT:PSS AND electrical characterization for the device PANI/PEDOT/paper, before and after exposed to steam HCI, process in which promoting the device doping, were realized using measures DC and impedance spectroscopy (EI). It shows that the results for the printing sytem PANI/PEDOT/paper can be modeled by an equivalent circuit comprising a resistor R in parallel with a capacitor C, both in series with another resistor r. Variations of each parameter were evaluated in function of exposure to different humidity percentage of the air (%RH) and ammonia concentrations (ppm and %). The resistor r contained in the equivalent circuit shown greater response and sensitivity to exposure as much moisture as gas ammonia showing the application feasibility of this system as printed sensor. An increased sensibility to the sytem PANI/PEDOT/paper (paper sensors) can be obtained by performing a heat treatment to promote evaporation of the excess of HCI in the system. For monitoring low concentrations of NH3, devices in PANI configuration PANI/PEDOT/PET (plastic sensors) demonstrated so much an better sensitive response low much an better time response compared to paper sensors treated thermally